Assessment of Genetic Variation of Genus Paracaryum (Boraginaceae) By Rapd Markers (Bangladesh Journal of Plant Taxonomy, 2022)
The present study reveals the genetic diversity of Iranian Paracaryum based on morphological and molecular characters of 12 species from 11 provinces of Iran. A total of 118 reproducible bands were generated by 10 of 30 random amplified polymorphic DNA (RAPD) primers, with an average of 11.8 bands per primer and 49% polymorphism. The largest number of effective alleles (Ne), Shannon Index (I) and genetic diversity (H) higher level of Shannon Index (I) and genetic diversity (H) were shown by Paracaryum persicum. Our data depicted the highest similarity between Paracaryum cyclhymenium and P. persicum and the lowest between P. sintenisii and P. bungei. P. bungei showed a relatively low level of genetic variation. Finally, the Neighbor Joining (NJ) trees based on RAPD markers data divided the populations into two different clusters, indicating their genetic difference, which is discussed in detail.Bangladesh J. Plant Taxon. 29(1): 31-41, 2022 (June)